Ethnic conflict in Nigeria: constitutional law and the dilemma of decision-making - Ray Ikechukwu Jacob; Suhana Saad (Faculty of Social Sciences and Humanities, UKM,Bangi, 2011)
﻿Ethnic conflicts may be triggered by factors such as geographical proximity, group identity, deliberate manipulation of negative perceptions by political leaders, competition of resources, weakness of political institution, and transitions to democracy. This paper enquires into how an ethnic conflict occurs as a result of actions or decisions made by either local or state / federal government in Nigeria. The main focus is the decision to implement the Sharia laws in Northern Nigeria, in particular, how it has led to bloody conflicts in the country. In-depth information materials gathered from informants were utilised to examine the scene of ethnic conflict in Nigeria. It was found that a number of violent events that had occurred in Nigeria was due to the manipulations of the constitutional law in a process of decision making by Muslims and Christian leaders and political elites that cannot fulfill the expectations of their respective ethnic groups.The consequences had been devastating in the forms of innumerous loss of lives, homes, destruction of properties and displacements. The economic consequences of the conflict were unequal distribution of resources among individuals, groups and regions within the nation. In conclusion, bad decision-making had led to ethnic conflicts in a highly charged ethnically polarised country such as Nigeria.